Research perspectives and challenges of blockchain for data-intensive and resource-constrained devices - Muhammad Imran; Bin Yao; Waqas Ali; Adnan Akhunzada; Muhammad Kashif Azhar; Muhammad Junaid; Uzair Iqbal (IEEE, 2022)
Blockchain technology in recent years has become potentially pervasive in the cryptocurrency market, thus providing tamper-proof security to decentralized transaction management systems. Structurally, the design foundation is an ideal advancement of the distributed ledger technology that maintains a set of global states across nodes. As technology expands with a higher trend towards mobile computing, the development of new applications demands understanding the current progression, especially concerning performance, data management, and storage prospects. Here, we report the principle design structure of the blockchain technology combined with the state of the arts, thus characterizing their original topological contexts. We depart from the fundamental concepts of the technology and analyze performance of the Ethereum blockchain on two devices having different computing power. Our presentation is tailored to provide a systematic review of the technology, thus facilitating their possible adoption into the new application domains like the Internet of Things (IoT). Further, we developed Debug-Bench, the first VSCode (Visual Studio Code) extension that enables benchmarking and profiling of the blockchain applications. Finally, we demonstrate several critical challenges concerning the design space of the current blockchain platforms for their implementation over resource-constrained devices.